Bilateral spontaneous chylothorax after severe vomiting in children - Rodrigues,Antonio Lucas Lima (2016)
Abstract Objective: To report the case of a child with bilateral chylothorax due to infrequent etiology: thoracic duct injury after severe vomiting. Case description: Girl, 7 years old, with chronic facial swelling started after hyperemesis. During examination, she also presented with bilateral pleural effusion, with chylous fluid obtained during thoracentesis. After extensive clinical, laboratory, and radiological investigation of the chylothorax etiology, it was found to be secondary to thoracic duct injury by the increased intrathoracic pressure caused by the initial manifestation of vomiting, supported by lymphoscintigraphy findings. Comments: Except for the neonatal period, chylothorax is an infrequent finding of pleural effusion in children. There are various causes, including trauma, malignancy, infection, and inflammatory diseases; however, the etiology described in this study is poorly reported in the literature.